The Horizontal Alignment Design Using AutocadÂ® Civil 3d on The Ciawi Tasikmalaya Regency Alternative Road - Yunita Hasna Faridah; Yusra Aulia Sari (Fakultas Teknik Sipil dan Perencanaan, 2023)
The choice of road lanes is a determining element in the financial improvement of a country. The mobility of suburban residents from isolated areas is linked to their economic activities by road construction, taking into account factors of comfort, safety, and smoothness of roads. Inside the geometric making plans of the road, it is important to decide the design standards that govern the vital elements of the road design. Computer software is used to facilitate and increase the level of planning precision. The author plans a horizontal alignment on Ciawi Tasikmalaya Regency Road using AutoCADÂ® Civil 3D in this geometric plan. Making this road aims to provide an alternative road by avoiding the congestion lane from the road that passes through the centre of the economy. This alternative road plan uses two SCS (Spiral-Circle-Spiral) type bends with a radius of 700 m, a design speed (Vr) of 80 km/hour, and a maximum slope of 6%.